Digital Transformation, Benefits and Impacts for Teenagers Study of Student Perceptions of Cybercrime in Yogyakarta State Islamic Senior High School Students - Muhani Jibi; Nur Aida; Mipasya Ratu Plamesti (STKIP Taman Siswa Bima, 2023)
Digital transformation in the field of education provides tremendous benefits for both teachers and students, enabling easy access to a wide range of knowledge and supporting the teaching and learning process, including distance learning. However, digital transformation has had an impact on students, as they often become victims of cybercrime in the form of cyberbullying, which affects the mental well-being of the individuals involved. The purpose of this research is to understand the perception of students at MAN (Madrasah Aliyah Negeri) in Yogyakarta regarding the digitally-based teaching and learning process that utilizes smartphones for activities outside of the classroom. The research method employed in this study is qualitative descriptive research, which involves gathering information about existing phenomena, clearly defining the objectives to be achieved, planning the approach, and collecting data as the basis for creating a report. The research findings indicate that students' perception of social media crime/cybercrime reflects their experiences as observers, perpetrators, and victims. Factors such as individual characteristics, environment, and friendships influence students in engaging in these criminal activities. Students tend to be loyal to their friends, and victims often choose to remain silent. Effective prevention measures have been implemented in schools through collaboration with law enforcement authorities.